KERJA SAMA SISTER CITY KOTA PADANG DENGAN KOTA HILDESHEIM BIDANG LINGKUNGAN TAHUN 2018-2022 - Puteri Sakinah Mantikasari Ag (2023)
This research discusses the cooperation carried out by the City of Padang, Indonesia and the City of Hildesheim, Germany within the framework of sister city cooperation in the environmental field in 2018-2022. The sister city collaboration between the City of Padang and the City of Hildesheim is a collaboration between city governments aimed at enhancing bilateral relations between the two cities which focus on work in the environmental sector which focuses on waste management in the City of Padang. In conducting this research analysis, the authors used descriptive qualitative methods and used the theory or concept of city and sister city diplomacy. In this study, data collection related to this research was carried out through interviews and literature study. The results of the study explained that this collaboration made a good contribution in the form of increasing the capacity of Padang City and achieving increased management and handling of waste problems. This study also explains that cooperation experiences problems related to funding, language communication processes.